Plantation forestry in Guanacaste, Costa Rica: a LUST description of plantation forestry (teak and melina) in Guanacaste, Costa Rica - Floors, A. (CATIE, Turrialba (Costa Rica). Atlantic Zone Programme Agricultural University Wageningen, Wageningen (Países Bajos) Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
2 fig. 8 tab. 18 ref. Sum. (En). También como Field Report - Atlantic Zone Programme (CATIE) no. 161